Halide Edib’s Anti-War Stance in Masks or Souls - Neslihan Günaydın Albay (Akademik Dil ve Edebiyat Dergisi, 2026)
In Masks or Souls written by a well-known woman novelist and feminist activist, Halide Edib Adıvar in 1945, the world problems and threats encountered are approached from the perspective of Nasreddin Hodja, one of the important figures of Turkish humor and philosophy in the thirteenth-century. Her being influenced by the philosophy of Nasreddin Hodja in Akşehir inspired her to write such a work in this style. The major people in the play are William Shakespeare and Nasreddin Hodja. Halide Edib develops a fantasy about sending these two personalities to the world after death, and events develop in this direction. Consisting of a prologue and four acts, Masks or Souls is a work in which fragmentary expression is preferred, which does not depend on time and space elements. Spaces can be classified as earth and the hereafter or earth and sky in general. Criticizing the top-down structure of the reforms and westernization process that took place immediately after the declaration of the Turkish Republic in 1923 throughout the play, Halide Edib closely experienced the material and spiritual two-way nature of people in the war environment as a person who personally experienced the destructive effects of wars on the shaping of the soul and body. During the voluntary exile period that she preferred during her maturity years, she saw the east and the west on her trips to America and India and made a comparison. She wanted to bring together the writers and personalities she was influenced by and reveal the true face of the human being hidden behind masks because the meanings of the concepts of “good” and “bad” are intertwined. The objective of this paper is to show how Masks or Souls epitomizes Halide Edib’s anti-war stance and pacifist nationalism as an example of anti-war literature.